Counterion effects on the ultrafast dynamics of charge-transfer-to-solvent electrons - Rivas, Nicolás (2017)
We performed femtosecond transient absorption (TA) experiments to monitor the solvation dynamics of charge-transfer-to-solvent (CTTS) electrons originating from UV photoexcitation of ammoniated iodide in close proximity to the counterions. Solutions of KI were prepared in liquid ammonia and TA experiments were carried out at different temperatures and densities, along the liquid-gas coexistence curve of the fluid. The results complement previous femtosecond TA work by P. Vöhringer's group in neat ammonia via multiphoton ionization. The dynamics of CTTS-detached electrons in ammonia was found to be strongly affected by ion pairing. Geminate recombination time constants as well as escape probabilities were determined from the measured temporal profiles and analysed as a function of the medium density. A fast unresolved (τ < 250 fs) increase of absorption related to the creation/thermalization of solvated electron species was followed by two decay components: one with a characteristic time around 10 ps, and a slower one that remains active for hundreds of picoseconds. While the first process is attributed to an early recombination of (I, e-) pairs, the second decay and its asymptote reflects the effect of the K+ counterion on the geminate recombination dynamics, rate and yield. The cation basically acts as an electron anchor that restricts the ejection distance, leading to solvent-separated counterion-electron species. The formation of (K+, NH3, e-) pairs close to the parent iodine atom brings the electron escape probability to very low values. Transient spectra of the electron species have also been estimated as a function of time by probing the temporal profiles at different wavelengths.